Margin Kontribusi, Titik Impas, Return on Innovation Telur asin Infus Daun Jintan Plectanthrus amboinicus) dan Cabe Merah - Sundari, Ristina Siti; Fitriadi, Budhi Wahyu; Hidayati, Reny (Universitas Galuh, 2026)
The potential for diversification of processed salted egg products that have high economic value is still wide Diversification of processed salted egg products with higher economic value still holds great potential. This is further enhanced by the advantage of not having a fishy odor. To increase competitiveness and added value, innovations in natural ingredients that enrich flavor and reduce fishy odor are needed. This study assessed the business feasibility of original salted egg products and variants infused with spicy cumin leaves and red chilies. The approach used was descriptive quantitative, with analysis of contribution margin, break-even point, and return on innovation. Data were collected from experiments conducted in the Agribusiness Laboratory, Faculty of Agriculture, Perjuangan University, Tasikmalaya. The salted egg formulation infused with cumin leaves (Coleus amboinicus) and red chilies showed positive effects in three dimensions: sensory, economic, and strategic. Sensorigraphically, there was a significant increase in herbal aroma, spiciness, and aftertaste, while simultaneously reducing the fishy odor, likely caused by volatile compounds in cumin leaves. Economically, this innovation generated net revenue of Rp792,777, a contribution margin of Rp4,409 per unit, a break-even point of only 0.21 eggs, and an ROI of 482.02%. The R/C ratio of 2.70 indicates high efficiency and commercial viability. The results suggest opportunities for premium pricing and/or production scale expansion, as both strategies increase profitability. This product possesses differentiation and comparative advantages, allowing it to be positioned as a gourmet or functional food with a spicy, red chili flavor profile.